Co-design of digital learning resources for care workers: reflections on the neurocare knowhow project. (18th August 2022) - Soreny, Cathy; Takhar, Philippa; Vickers, Emma; Bartlett, Rebecca; Coates, Elizabeth; Stavroulakis, Theocharis; Fox, Emily; Davidson, Heather; Harrison, Adam; McDermott, Christopher
Abstract: Neurocare Knowhow is an online learning platform for care workers who support people with neurological conditions. Care workers often do not receive specialist training around neurological conditions and can experience anxiety and apprehension about caring for this group. Neurocare Knowhow aims to increase care workers' knowledge and confidence. Featuring flexible and personalisable digital features, in combination with documentary video and audio, it offers an alternative to traditional e-learning, moving away from longform didactic courses to flexible on-the-go learning. This co-design project worked closely with people with neurological conditions, their families, care workers and care organisation managers to validate the need and develop a proof of concept pilot. Co-design activity took place across multiple workshops in person and online. These gathered detailed insights into preferred features that support engaging online learning. The platform offers learning across diverse neurological conditions as a whole, with a focus on shared symptoms and challenges encountered by people with neurological conditions. Ongoing development to scale the pilot up to meet an anticipated national audience includes a focus on artificial intelligence to support searches at a moment of need and a range of personalisable features for individual and team learning.